1995
DOI: 10.1152/ajpregu.1995.268.2.r375
|View full text |Cite
|
Sign up to set email alerts
|

Systemic hemodynamics and renal function during long-term pathophysiological increases in circulating endothelin

Abstract: Although recent studies have reported endogenous plasma endothelin levels to be elevated two- to fivefold in chronic pathophysiological states, whether such an increase in circulating endothelin levels alone can lead to significant long-term alterations in cardiovascular and renal function is not known. The purpose of this study was to examine the long-term systemic hemodynamic and renal effects of a pathophysiological increase in plasma endothelin concentration in chronically instrumented, conscious dogs (n =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
31
0
2

Year Published

1996
1996
2012
2012

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 0 publications
2
31
0
2
Order By: Relevance
“…39,40 Endothelin also stimulates oxidative stress by causing upregulation of the subunits of NAD(P)H oxidase and increasing superoxide. 41 In postmenopausal women, plasma endothelin levels have been shown to be increased.…”
Section: Does Endothelin Play a Role In Postmenopausal Hypertension?mentioning
confidence: 99%
See 1 more Smart Citation
“…39,40 Endothelin also stimulates oxidative stress by causing upregulation of the subunits of NAD(P)H oxidase and increasing superoxide. 41 In postmenopausal women, plasma endothelin levels have been shown to be increased.…”
Section: Does Endothelin Play a Role In Postmenopausal Hypertension?mentioning
confidence: 99%
“…Endothelin is a potent vasoconstrictor that, when administered on a long-term basis, causes increases in sodium reabsorption in the kidney 39 and increases blood pressure. 39,40 Endothelin also stimulates oxidative stress by causing upregulation of the subunits of NAD(P)H oxidase and increasing superoxide.…”
Section: Does Endothelin Play a Role In Postmenopausal Hypertension?mentioning
confidence: 99%
“…Interestingly, in vivo studies revealed that administration of ET-1 resulted in reduced renal hemodynamics and kidney dysfunction, similar to those found during pneumoperitoneum (9). For instance, whole organ studies in intact rats have demonstrated that a shortlasting infusion of ET-1 into the renal artery decreases renal plasma flow (RPF), GFR, and urine volume (5,22,38,46). Similarly, a long-term infusion of ET-1 into conscious dogs results in increased renal vascular resistance and decreased GFR and RPF (5,46).…”
mentioning
confidence: 99%
“…For instance, whole organ studies in intact rats have demonstrated that a shortlasting infusion of ET-1 into the renal artery decreases renal plasma flow (RPF), GFR, and urine volume (5,22,38,46). Similarly, a long-term infusion of ET-1 into conscious dogs results in increased renal vascular resistance and decreased GFR and RPF (5,46). Hence, it is proposed that activation of the ET system may be involved in pneumoperitoneum-induced renal dysfunction.…”
mentioning
confidence: 99%
“…47 In contrast, endothelial ET B stimulation acts as an opposing vasodilator, by enhancing the synthesis of relaxing compounds, such as nitric oxide and prostaglandins. 48 In the kidney, locally generated endothelin produces ET A -mediated vasoconstriction and antinatriuresis 49 but also very important ET B -mediated diuresis and natriuresis via inhibition of vasopressin-induced synthesis of cyclic AMP, 50 and of the activity of tubular Na + /K + ATPase. 51 Endothelins were discovered and described predominantly as pressor agents.…”
Section: Endothelins and Bp Regulationmentioning
confidence: 99%